The Parental Monitoring Guideline for Reducing Adolescent Alcohol Use - Jewpattanakul, Yupa; Reunthongdee, Ubolwanna; Tubkeaw, Titirut (Nursing Science Journal of Thailand, 2013)
Purpose: To develop a parental monitoring guideline for reducing alcohol use in Thai adolescents. Design: A qualitative research design. Method: The study area was divided based on its geographical location into 3 groups. Eight eligible parents were recruited to be the study sample for each group, totally 24. Focus group was conducted once for each group. Content analysis was performed to draft the parental monitoring guideline. Then, public reviews of the guideline draft were performed twice with 172 villagers in the study area for revision. Main findings: Five themes were emerged as follows: 1) communication about risk of alcohol consumption, reduction of alcohol use, and social relation without alcohol; 2) appropriate parental supervision; 3) family relationships; 4) peer influence; 5) avoidance of approaching alcohol advertisement. Conclusion and recommendations: The guideline should be used for developing a program for enhancing parenting skills in monitoring their children regarding alcohol consumption. In particular, communication skills within family, techniques of building family relations and monitoring the teens’ behavior should be taught in the program. Keywords: parental monitoring, alcohol use, adolescent บทคัดย่อ วัตถุประสงค์: เพื่อพัฒนาแนวทางการเฝ้าระวังจากบิดา-มารดาเพื่อลดการบริโภคเครื่องดื่มแอลกอฮอล์ของเยาวชนไทย รูปแบบการวิจัย: การวิจัยเชิงคุณภาพ วิธีดำเนินการวิจัย: แบ่งพื้นที่ในตำบลที่ศึกษาตามเขตภูมิศาสตร์ออกเป็น 3 กลุ่ม และเลือกบิดาหรือมารดาที่มีคุณสมบัติตามเกณฑ์ที่กำหนดมากลุ่มละ 8 คน รวมเป็น 24 คน เก็บรวบรวมข้อมูลโดยการสนทนากลุ่มบิดา-มารดา กลุ่มละ 1 ครั้ง แล้วทำการวิเคราะห์ข้อมูลโดยการวิเคราะห์เชิงเนื้อหา และจัดเวทีประชาคม 2 ครั้ง โดยมีชาวบ้าน 172 คนเข้าร่วมเพื่อปรับแก้แนวทางการเฝ้าระวังจากบิดา-มารดาเพื่อลดการบริโภคเครื่องดื่มแอลกอฮอล์ของเยาวชน ผลการวิจัย: บิดา-มารดาเสนอแนะแนวทางการเฝ้าระวังเพื่อลดการบริโภคเครื่องดื่มแอลกอฮอล์ของเยาวชนไว้ 5 ประเด็น ได้แก่ 1) การสื่อสารเกี่ยวกับการบริโภคเครื่องดื่มแอลกอฮอล์ ในเรื่องความเสี่ยงที่เกิดจากการบริโภคเครื่องดื่มแอลกอฮอล์ วิธีการลดบริโภคเครื่องดื่มแอลกอฮอล์ และวิธีการเข้าสังคมโดยไม่จำเป็นต้องบริโภคเครื่องดื่มแอลกอฮอล์ 2) บิดา-มารดาควรควบคุมพฤติกรรมของเยาวชนอย่างเหมาะสม 3) การสร้างสัมพันธภาพในครอบครัว 4) การเลือกคบเพื่อน และ 5) พยายามให้เยาวชนหลีกเลี่ยงการดูสื่อโฆษณาเครื่องดื่มแอลกอฮอล์ สรุปและข้อเสนอแนะ: ควรนำแนวทางการเฝ้าระวังที่ได้เป็นข้อมูลในการพัฒนาโปรแกรมที่เสริมสร้างทักษะการเฝ้าระวังแก่บิดา-มารดา เพื่อลดการบริโภคเครื่องดื่มแอลกอฮอล์ของเยาวชน โดยมุ่งเน้นการฝึกทักษะการสื่อสารภายในครอบครัว เทคนิคการสร้างสัมพันธภาพที่ดีระหว่างสมาชิกในครอบครัว และเทคนิคการควบคุมพฤติกรรมบุตร คำสำคัญ: การเฝ้าระวังจากบิดามารดา การบริโภคเครื่องดื่มแอลกอฮอล์ เยาวชน